Selected aspects of attitudes of health care professionals towards nurses - Skorupska, Agnieszka; Machowicz, Aldona (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. Current nursing care emphasizes both professional and scientific development. One of important, however not the only one, predictors of such development includes popularization of nurse education - Bachelor of Science in nursing and Master of Science in nursing. Quality of delivered care, which should be creative and autonomic, becomes measure of effectiveness of changes observed during that process. It may also be assumed that cooperation of therapeutic team members is significant for the whole of achieved therapeutic goals. On the other hand, such cooperation results from attitudes presented by members of this team toward each other. Aim of the study. Therefore, this work attempts to evaluate attitudes of medical and non-medical professionals of health care toward nurses. Material and methods. The total number of respondents was 130 (30 participants were employed in hospital administration, 32 medical rescuers, 31 rehabilitation specialists, and 37 midwives) who filled self-evaluation survey questionnaire. Results and conclusions. Obtained data allowed the authors to assume that nurses are perceived by other professionals as competent, independent, trustful, however financially underappreciated, medical specialists. According to respondents nursing is an independent scientific discipline whereas conducting research work creates opportunities for additional professional education, which may further establish Nursing position among other medical sciences. Nursing Topics 2010; 18 (1): 53-59